REM Sleep Characteristics in Narcolepsy and REM Sleep Behavior Disorder - Dauvilliers, Yves (Associated Professional Sleep Societies, LLC, 2007)
STUDY OBJECTIVES: To assess the presence of polysomnographic characteristics of REM sleep behavior disorder (RBD) in narcolepsy; and to quantify REM sleep parameters in patients with narcolepsy, in patients with “idiopathic” RBD, and in normal controls. DESIGN: Sleep laboratory study PARTICIPANTS: Sixteen patients with narcolepsy and cataplexy matched for age and sex with 16 patients with “idiopathic” RBD and with 16 normal controls were studied. MEASUREMENTS AND RESULTS: Higher percentages of REM sleep without atonia, phasic electromyographic (EMG) activity, and REM density were found in patients with narcolepsy than normal controls. In contrast, RBD patients had a higher percentage of REM sleep without atonia but a lower REM density than patients with narcolepsy and normal controls. Based on a threshold of 80% for percentage of REM sleep with atonia, 50% of narcoleptics and 87.5% of RBD patients had abnormal REM sleep muscle activity. No significant behavioral manifestation in REM sleep was noted in either narcoleptics or controls. We also found a higher frequency of periodic leg movements during wake (PLMW) and during sleep (PLMS) in narcoleptic patients compared to controls. CONCLUSIONS: The present study demonstrates abnormalities in REM sleep motor regulation with an increased frequency of REM sleep without atonia, phasic EMG events and PLMS in narcoleptic patients when compared to controls. These abnormalities were seen more prominently in patients with RBD than in narcoleptics, with the exception of the PLMS index. We proposed that dysfunctions in hypocretin/dopaminergic system may lead to motor dyscontrol in REM sleep that results in dissociated sleep/wake states. CITATION: Dauvilliers Y; Rompré S; Gagnon JF et al. REM sleep characteristics in narcolepsy and REM sleep behavior disorder. SLEEP 2007;30(7):844-849.